PEMBERIAN OBAT OLEH PENGAWAS MINUM OBAT SEBAGAI DETERMINAN KEBERHASILAN PENGOBATAN TUBERCULOSIS ANAK DI KOTABUMI SELATAN: STUDI KUALITATIF - Zenni Puspitarini; Rina Mariani; Hasti Primadilla Kusumaningrum; Imam Budi Pratomo (Jurnal Keperawatan Widya Gantari Indonesia, 2026)
Indonesia ranks second global in contributing to tuberculosis (TB) cases, a life-threatening disease that significantly affects child growth and development, particularly among children under two years of age. Given the high risk of morbidity and mortality in this age group, the role of the Treatment Observer (Pengawas Minum Obat / PMO) is highly strategic and plays crucial role in monitoring treatment adherence to ensure successful recovery. This study aimed to identify specific patterns in the mechanisms of medication administration by treatment observers for pediatric TB patients during home-based treatment in South Kotabumi, Lampung Province. This study employed a descriptive qualitative design, with a sample consisting of PMOs of children aged 0-18 years diagnosed with TB, involving a total five respondents. The study was conducted from July to October 2025 in the working area of Kotabumi 2 Public Health Center. Data validity was ensured through triangulation. The findings revealed several medication administration patterns, including daily monitoring, medication schedule reminders, psychosocial approaches, time flexibility, and community collaboration. These medication administration patterns contribute to the success of TB treatment in children.